2002
DOI: 10.1016/s0022-5347(05)64579-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Laparoscopic Neobladder

Abstract: To our knowledge we report the first case of laparoscopic radical cystectomy with ileal orthotopic reconstruction. This original technique combines the advantages of minimally invasive laparoscopy with the speed and safety of open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 14 publications
0
19
0
2
Order By: Relevance
“…However, numerous reports showed success with the procedure in addition to success with urinary diversion methods [15,16,17,18,19]. Centers reported successful results with intra- and extracorporeal urinary diversion [15,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, numerous reports showed success with the procedure in addition to success with urinary diversion methods [15,16,17,18,19]. Centers reported successful results with intra- and extracorporeal urinary diversion [15,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…Researchers would agree that extracorporeal diversion is associated with decreased operation time, while also providing a more secure anastomosis [20]. As in the study of Gaboardi et al [20], we performed all the diversions as extracorporeal procedures. Leakage from anastomosis was seen in 3 patients of our study group (2 in LRCP, 1 in ORCP).…”
Section: Discussionmentioning
confidence: 99%
“…A 5 cm supraumbilical incision was chosen after anatomical studies in cadavers showed that it provides sufficient access to isolate the intestinal loop and restore bowel continuity. 17 The same incision was used to de-liver a terminal ileum onto the surface and construct the urinary diversion in the standard hand-sewn way. It helps to ensure the preservation of bowel vascularization during isolation of the ileal loop due to the use of transillumination and to prevent future intestinal mechanical obstruction due to the re-approximation of mesenteric margins.…”
Section: Discussionmentioning
confidence: 99%
“…La parte más compleja de la cirugía, está representada por la elabora- También se han publicado series con derivaciones urinarias continentes realizadas con técnica completamente laparoscópica [52][53][54] . Series recientes de cistectomía radical laparoscópica muestran bajas tasas de complicaciones, aunque la experiencia acumulada aún no es suficiente para compararlas frente a la cirugía abierta.…”
Section: Cistectomía Radicalunclassified